Improving the Performance of Residents in Pediatric Resuscitation with Frequent Simulated Codes - Sule Doymaz MD; Munaza Rizvi MD; Clara Giambruno MD, MPH (SAGE Publishing, 2020)
Aim . Exposure to real codes during pediatric residency training is scarce. Consequently, experiencing mock codes scenarios can provide an opportunity to increase residents' confidence and knowledge in managing pediatric emergencies. Hypothesis . Pediatric senior residents perform better as code team leaders if they are exposed to frequent mock codes. Material and Methods . Forty-three pediatric senior residents (postgraduate year [PGY] two and three) participated in the study. Team leader performance was assessed utilizing the Team Emergency Assessment Measure (TEAM) scoring. Residents' team leadership performance was assessed before and 6 months after the implementation of weekly mock codes. Results . Pediatric residents' team leadership performance in mock codes improved after exposure to weekly practice mock code sessions (71.93 ± 18.50 vs 81.44 ± 11.84, P  = 0.01). Conclusion . Increasing the frequency of mock code sessions during residency training led to an improvement in code team leadership performance in pediatric senior residents.